Optimalisasi Pembiayaan Mudharabah Pada Bank Syariahdi Indonesia - Ni’mah, Jamilatun; Kusumaningrum, Budiani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research is motivate d by the fact that Islamic banks in Indonesia are currently not optimal in channeling mudharabah financing. Islamic bank financing in Indonesia is still dominated by murabaha financing. The purpose of this study is to discuss in depth regarding the optimization of mudharabah financing in Islamic banks in Indonesia. A qualitative research approach is used in this research. This research uses secondary data or literature study. This study uses the qualitative data analysis technique modeled by Miles and Huberman. The results of this study indicate that if the percentage of mudharabah financing in Islamic banks in Indonesia is still relatively small, people tend to use murabahah financing rather than mudharabah financing. Then from the side of Islamic banks in Indonesia so far they have been trying to maximize the distribution of mudharabah financing. Keywords: optimization, mudharabah financing, islamic banks.